1998
DOI: 10.1359/jbmr.1998.13.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc Supplementation on Vertebral and Femoral Bone Mass in Rats on Strenuous Treadmill Training Exercise

Abstract: The hypothesis that a zinc (Zn) deficit may cause osteopenia in athletes is well founded. In rats exposed to strenous exercise, we evaluated the effect of a zinc supplement on femoral and vertebral bone mass determined by dual-energy X-ray absorptiometry. Four lots of 93-day-old female Wistar rats were studied. A control group of 30 rats were not manipulated (Zn-Ex-group). The experimental group of 40 rats was fed a diet supplemented with an additional 20% of Zn/kg of feed; this group was divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
(45 reference statements)
5
14
0
Order By: Relevance
“…Because of the influence of weight on bone mass [11], femur BMC was corrected for the animals final body weight (femur BMC/FW mg/g). As in our earlier studies [11][12][13][14], we have relied on DXA (Norland XR-26, Norland Co., Fort Atkinson, Wisconsin, USA). Our coefficients of variation (CV) for the current measurements, determined by six separate measurements done on three rat femurs and 5th vertebras at intervals of 3-4 days were 0.8% and 0.7%, respectively.…”
Section: Morphometric and Densitometric Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the influence of weight on bone mass [11], femur BMC was corrected for the animals final body weight (femur BMC/FW mg/g). As in our earlier studies [11][12][13][14], we have relied on DXA (Norland XR-26, Norland Co., Fort Atkinson, Wisconsin, USA). Our coefficients of variation (CV) for the current measurements, determined by six separate measurements done on three rat femurs and 5th vertebras at intervals of 3-4 days were 0.8% and 0.7%, respectively.…”
Section: Morphometric and Densitometric Studiesmentioning
confidence: 99%
“…The usefulness of dual-energy X-ray absorptiometry (DXA) for bone-mass determinations in small animals has been validated repeatedly [10] and our team had relied extensively on this technique in previous experimental studies [11,12]. More recently [13], we have demonstrated that zinc exerts a powerful influence by inhibiting the loss of bone mass in rats subjected to strenuous physical exercise. In view of these assertions, the present study was centered on the verification of the effect of Si on the bone mass loss through ovariectomy practiced on rats.…”
mentioning
confidence: 99%
“…In female rats strenuously exercising on a treadmill the length, weight, bone mineral content (BMC), and bone mineral density (BMD) of the femur was lower in animals receiving a normal diet, compared to those receiving a zinc supplemented diet 47 .…”
Section: Is There An Interaction Between Exercise and Diet?mentioning
confidence: 99%
“…Attempts to remedy low BMD in men through nutritional interventions have included zinc (Zn), with dietary Zn intake and plasma Zn both having a positive association with BMD [14]. Additionally, dietary Zn has been shown to improve BMD in humans [14][15][16][17][18] and in rats [19][20][21][22]. However, the influences of variations in Zn bioavailability and voluntary exercise levels as well as the associated combined effects of these influences on BMD have not been well documented.…”
Section: Introductionmentioning
confidence: 99%